Technology News - No. 502 - A New Training Video for Aggregate Operators "Aggregate Training for the Safety Impaired" (The National Institute for Occupational Safety and Health (NIOSH), 2003)
Objective To develop safety training tools for mine safety and health trainers that can be used for both new-miner training and annual refresher training. Background For the past 3 years, NIOSH has been developing training materials for mine safety trainers in response to gaps identified during stakeholder meetings. Most materials have been directed to the hazards of underground mines, but the recent passage of Part 46 of CFR 30 required new-miner and annual refresher training in aggregate operations. One result was the identification of another audience needing basic information about safety in mining. Trainers characterized trainees in this segment of the industry primarily as young males, many of whom had little work experience. Approach Training specialists from the Arizona State Mine Inspector’s Office approached NIOSH researchers early in2002 about the possibility of a collaborative project to develop safety training materials for new trainees in aggregate operations. A preliminary search of MSHA accident statistics identified over a dozen common hazards that could be targeted in a training video. A storyline was developed for review by safety specialists in the aggregate industry, and a script was written to cover the selected hazards. Although the target audience was primarily new hires, the finished video was also to be relevant to more experienced workers.